Financial Performance and Stock Prices in Tourism & Hospitality: Kinerja Keuangan dan Harga Saham dalam Industri Pariwisata & Perhotelan - Vivanda Adi Prima Suryo; Herlinda Maya Kumala Sari (Academia Open, 2024)
This study utilizes a quantitative approach to examine the relationship between financial performance indicators (ROA, ROE, EPS, and OPM) and stock prices in the tourism and hospitality sector from 2018 to 2021. Secondary data, sourced from the Indonesian Stock Exchange (BEI) containing annual financial reports of listed companies, was analyzed using Multiple Linear Regression. The results indicate that ROA and ROE do not significantly affect stock prices, while EPS has a positive and significant impact, supporting Hypothesis 3. OPM, however, does not demonstrate a significant influence on stock prices, contradicting Hypothesis 4. These findings emphasize the critical role of earnings per share (EPS) in evaluating stock performance in the sector. Highlight: This study examines the relationship between financial performance indicators (ROA, ROE, EPS, OPM) and stock prices in the tourism and hospitality sector. Results indicate that ROA and ROE do not significantly impact stock prices, while EPS plays a crucial role. OPM was found to have no significant influence on stock prices, suggesting EPS is a vital metric for assessing stock performance in this industry. Keywords: Quantitative Analysis, Financial Performance, Stock Prices, Tourism and Hospitality, Earnings per Share (EPS)